SARS-CoV-2 vaccination and infection in ozanimod-treated participants with relapsing multiple sclerosis - Cree, Bruce A C; Maddux, Rachel; Bar-Or, Amit; Hartung, Hans-Peter; Kaur, Amandeep; Brown, Elizabeth; Li, Yicong; Hu, Yanhua; Sheffield, James K; Silva, Diego; Harris, Sarah (Annals of clinical and translational neurology, 2023)
OBJECTIVE: To investigate the serologic response, predictors of response, and clinical outcomes associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination and infection in ozanimod-treated participants with relapsing multiple sclerosis (RMS) from DAYBREAK. METHODS: DAYBREAK (ClinicalTrials.gov-NCT02576717), an open-label extension study of oral ozanimod 0.92 mg, enrolled participants aged 18-55 years with RMS who completed phase 1-3 ozanimod trials. Participants who were fully vaccinated against SARS-CoV-2 with mRNA or non-mRNA vaccines, were unvaccinated, and/or had COVID-19-related adverse events (AEs, with or without vaccination) and postvaccination serum samples were included (n = 288). Spike receptor binding domain (RBD) antibody levels (seroconversion: ≥0.8 U/mL) and serologic evidence of SARS-CoV-2 infection (nucleocapsid IgG: ≥1 U/mL) were assessed (Roche Elecsys/Cobas e411 platform). RESULTS: In fully vaccinated participants (n = 148), spike RBD antibody seroconversion occurred in 90% (n = 98/109) of those without serologic evidence of prior SARS-CoV-2 exposure (100% [n = 80/80] seroconversion after mRNA vaccination) and in 100% (n = 39/39) of participants with serologic evidence of viral exposure. mRNA vaccination predicted higher spike RBD antibody levels, whereas absolute lymphocyte count (ALC), age, body mass index, and sex did not. COVID-19-related AEs were reported in 10% (n = 15/148) of fully vaccinated participants-all were nonserious and not severe; all participants recovered. INTERPRETATION: Most ozanimod-treated participants with RMS mounted a serologic response to SARS-CoV-2 vaccination and infection, regardless of participant characteristics or ALC levels. In this analysis, all COVID-19-related AEs post-full vaccination in participants taking ozanimod were nonserious and not severe.
Keywords: Vaccination; COVID-19; RNA, Messenger; vakcinace; Humans; vakcíny proti COVID-19; roztroušená skleróza; lidé; SARS-CoV-2; messenger RNA; Multiple Sclerosis; COVID-19 Vaccines